Microbiome Dynamics of a Polychlorobiphenyl (PCB) Historically Contaminated Marine Sediment under Conditions Promoting Reductive Dechlorination - Matturro, Bruna; Ubaldi, Carla; Rossetti, Simona (Frontiers in Microbiology, 2016)
The toxicity of polychlorinated biphenyls (PCB) can be efficiently reduced in contaminated marine sediments through the reductive dechlorination process lead by anaerobic organohalide bacteria. Although the process has been extensively investigated on PCB-spiked sediments, the knowledge on the identity and metabolic potential of PCB-dechlorinating microorganisms in real contaminated matrix is still limited. Aim of this study was to explore the composition and the dynamics of the microbial communities of the marine sediment collected from one of the largest Sites of National Interest (SIN) in Italy (Mar Piccolo, Taranto) under conditions promoting the PCBs reductive dechlorination. A long-term microcosm study revealed that autochthonous bacteria were able to sustain the PCB dechlorination at a high extent and the successive addition of an external fermentable organic substrate (lactate) caused the further depletion of the high-chlorinated PCBs (up to 70%). Next Generation Sequencing was used to describe the core microbiome of the marine sediment and to follow the changes caused by the treatments. OTUs affiliated to sulfur-oxidizing ε-proteobacteria, Sulfurovum and Sulfurimonas, were predominant in the original sediment and increased up to 60% of total OTUs after lactate addition. Other OTUs detected in the sediment were affiliated to sulfate reducing (δ-proteobacteria) and to organohalide respiring bacteria within Chloroflexi phylum mainly belonging to Dehalococcoidia class. Among others, Dehalococcoides mccartyi was enriched during the treatments even though the screening of the specific reductive dehalogenase genes revealed the occurrence of undescribed strains, which deserve further investigations. Overall, this study highlighted the potential of members of Dehalococcoidia class in reducing the contamination level of the marine sediment from Mar Piccolo with relevant implications on the selection of sustainable bioremediation strategies to clean-up the site.